Food Safety and Halal Risk Mitigation in Fish Crackers Supply Chain with FMECA and AHP - Wafika Urfah Maulidah; Hana Catur Wahyuni (Procedia of Engineering and Life Science, 2021)
With the development of the times, people are increasingly aware that food is safe for consumption. Throughout the food supply chain process, there are many risks of food safety from being safe to being unsafe. This study aims to analyze food safety and halal risk mitigation in the supply chain, which consists of identifying food safety risks throughout the supply chain process, measuring food safety risks in the supply chain, determining the most critical value for risks that arise in food safety, and determining food safety risk mitigation measures. The object used is the supply chain of fish cracker companies in the Buduran area, Sidoarjo. Data processing was performed using FMECA and AHP methods. The results showed that the most critical risk lies in the management of the meat grinding system with a value of 0.60494 where the influencing factors are the absence of halal certification on the product and not implementing food safety standards, so that mitigation measures are carried out, namely evaluating and fostering manpower planning and job analytic.